PENGARUH DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DANA BAGI HASIL, DAN DANA KEISTIMEWAAN TERHADAP TINGKAT KEMANDIRIAN KEUANGAN DAERAH - Hari Sugiyanto Sugiyanto; Anikmah Musfirati (Politeknik Keuangan Negara STAN, 2021)
This study aims to examine the effect of General Purposed Transfer, Special Purposed Transfer, Revenue Sharing, and Special Fund on district/city level of regional fiscal independence, especially in Special region of Yogyakarta (DIY). Data analysis using panel data regression with fixed effect model and Generalized Least Square method. The research sample is all districts/cities in Special Region of Yogyakarta (total sampling) that have realized the DAU, DAK, DBH, Special Fund and also the components forming the ratio of regional fiscal independence in 2013 to 2019. The result shows that DAU has a significant negative effect on the level of regional fiscal independence. DAK and Special Fund have a significant positive effect on the level of regional fiscal independence. Meanwhile, DBH has no effect on the level of regional fiscal independence.